Impact of Precision Medicine on Clinical Outcomes: A Single-Institution Retrospective Study - Quinn, Ryann; Patel, Rajvi; Sison, Cristina; Singh, Amandeep; Zhu, Xin-Hua (Frontiers in Oncology, 2021)
Purpose The strategy of precision medicine has been widely adopted in the practice of oncology, although the efficacy remains unclear. This study assesses clinical outcomes in patients with an actionable alteration found during FoundationOne CDx™ (F1CDx) testing and who received a targeted therapy based on the results. Materials and Methods This is a retrospective cohort study of patients with tumors that underwent F1CDx from September 2012 to July 2018. F1CDx provided actionable alterations for patients to select appropriate therapies. The primary objective was to estimate the objective response rate (ORR) at 3 months from the start of study treatment. The secondary objectives were to estimate progression-free survival (PFS) and overall survival (OS). Results One thousand patients underwent F1CDx testing. Six hundred fifty-two patients were identified as having actionable mutations. Thirty-eight patients (18 males and 20 females) received targeted therapy and were included in the study. The most common alterations were PD-1/PDL-1, high-TMB, P13K, and HER2/ERBB2. Patients received various treatments including nivolumab, pembrolizumab, trastuzumab, and everolimus. Eight (23.5%) and six (17.7%) patients achieved partial response (PR) and stable disease (SD), respectively; 20 (58.8%) had progression of disease (PD). The disease control rate was 41.2% (95% CI: 24.7% to 59.3%). The median PFS was 2.7 months (95% CI: 2.3 to 5.4 months), and median OS was 9.9 months (95% CI: 4.5 to 33.7 months). Conclusion Our results demonstrate promising data in precision medicine in real community oncology practice. It warrants further large and prospective studies in patients with actionable alterations.